2021
DOI: 10.7759/cureus.14528
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Vitamin D Levels and Its Correlation With Low Birth Weight in Neonates: A Tertiary Care Hospital Experience in Saudi Arabia

Abstract: IntroductionA meta-analysis showed that 63.6% of the Saudi population have vitamin D deficiency, including many pregnant women. Studies showed that maternal vitamin D deficiency during pregnancy is a risk factor for low birth weight (LBW) in neonates. Neonatal LBW is a risk factor for multiple neonatal complications including respiratory distress syndrome, necrotizing enterocolitis, chronic renal disorders, seizures, and sepsis. Our objective in this study is to determine a correlation between low maternal vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…VD deficiency has been linked to a higher risk of low birth weight (22) . Statistically, this study found no association between maternal VDLs and LBW; according to Almidani et al (23) , there is no link between VD in the mother and the infant's birth weight. However, the mean VDLs of mothers with newborns of average weight are higher.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…VD deficiency has been linked to a higher risk of low birth weight (22) . Statistically, this study found no association between maternal VDLs and LBW; according to Almidani et al (23) , there is no link between VD in the mother and the infant's birth weight. However, the mean VDLs of mothers with newborns of average weight are higher.…”
Section: Discussioncontrasting
confidence: 52%
“…Vitamin D's extraskeletal roles in embryonic development have been the subject of recent studies. These roles include adipogenesis, cell proliferation, glucose homeostasis, and immunomodulation (23,28) . VDLs in the mother was observed to have strong associations with the Apgar scores of their newborns; higher levels were associated with better Apgar score.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to all of the above, Thompson et al [23], who assessed the causal effects of maternal 25(OH)D levels and calcium supplementation on offspring birth weight in pregnancy, found no effect on birth weight in otherwise healthy neonates. The study by Almidani et al [24] reached a similar conclusion; the association of neonatal birth weight with maternal 25(OH)D levels during pregnancy was statistically insignificant for both early term (after 37 + 0 to 38 + 6 weeks of gestation) and full-term infants (after 39 to 40 weeks of gestation). The clinical study by Hajhashemi et al [25] tested the administration of a higher vitamin D dose supplement of 4000 IU/day for 10 weeks in pregnant women with VDD.…”
Section: Introductionmentioning
confidence: 65%
“…Another study, conducted in Riyadh, confirmed that 60% of women were deficient in vitamin D [20]. Almidani et al [102] confirmed that 87.4% of mothers had a vitamin D deficiency during pregnancy. A study from the Al-Jouf region confirmed that 70% of pregnant women are deficient in vitamin D [103].…”
Section: Discussionmentioning
confidence: 92%
“…This is why serum and molecular studies on vitamin D, as well as the VDR, show variable results within the kingdom. Limited studies have been conducted in Saudi women diagnosed with GDM, and SNPs in the VDR gene [43][44][45] and serum levels [22,34,102,145] were studied separately. In the current study, we integrated serum levels and SNPs of the VDR gene and presented a combined treatment in women with GDM.…”
Section: Discussionmentioning
confidence: 99%